Can Volunteered Geographic Information Be a Participant in eEnvironment and SDI? - Mooney, Peter; Corcoran, Padraig (Environmental Software Systems. Frameworks of eEnvironment, 2011)
We investigate the potential role Volunteered Geographic Information (VGI) can play in eEvironment and various Spatial Data Infrastructures (SDI) on a local, regional, and national level. eEnvironment is the use and promotion of ICT for the purposes of environmental assessment and protection, spatial planning, and the sustainable use of natural resources. An SDI provides an institutionally sanctioned, automated means for posting, discovering, evaluating, and exchanging geospatial information by participating information producers and users. A key common theme shared by both definitions is public participation and user-centric services. We pose the research question: is VGI (an example of public participation and collaboration) is ready to participate in eEnvironment and SDI?